ANALISIS PERGESERAN KATEGORI PADA FRASA BERPREPOSISI DALAM SEBUAH NOVEL BERJUDUL “UGLY LOVE” - Sunarti Desrieny Tambunan (Jurnal Sosial Humaniora dan Pendidikan, 2024)
The purpose of this study is to identify the category shifts employed by the translator in translating prepositional phrases in a novel titled *"Ugly Love"* from English into Indonesian. A qualitative descriptive method was used in this research. The findings reveal that, specifically in Chapter 1 of the novel, eight (8) instances of category shifts were identified, consisting of one (1) structural shift, two (2) class shifts, three (3) unit shifts, and two (2) intra-system shifts. When translating phrases, structural shifts are the most common occurrences in the Indonesian language. However, based on the findings, prepositional phrases are translated in the translator's style without altering the meaning of the source language, ensuring that the results remain accurate and acceptable.